Vegetable simple - Ripert, Eric (Random House, 2020)
"Eric Ripert is the co-owner of the acclaimed restaurant Le Bernadin, and the winner of countless Michelin stars. He is well known for his exquisite, clean, seafood-centered cuisine, but now, in Vegetable Simple, he turns his singular culinary imagination to vegetables. Lately, Ripert has found himself reaching for vegetables as his main food source - and doing so, as is his habit, with great intent and care. In the 110 recipes in this book, Ripert brings out their beauty; their earthiness, their nourishing qualities, and the many ways they can be prepared. From his sweet pea soup to his watermelon pizza, from his fava bean and mint salad to his mushroom Bolognese and his roasted carrots with harissa, Eric Ripert articulates a vision for vegetables that are prepared simply, without complex steps or ingredients, allowing their essential qualities to shine and their color and flavor to remain uncompromised. A gorgeous guide to the way we eat today"--